Penerapan Program Ekstrakurikuler Bahasa Inggris sebagai Bahasa Asing Permulaan pada anak usia 4-5 tahun di Tk Muslimat NU 200 Kureksari - Maulidah Mega Cantika Soviana Dhowi; Ilun Muallifah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This research aims to explore the implementation of an English extracurricular program as an initial foreign language for children aged 4-5 years at TK Muslimat NU 200 Kureksari. Through this program, it is expected that children can be introduced to English in a fun, interactive, and developmentally appropriate manner. This study uses a qualitative method with a case study approach. Data were collected through observation, interviews, and document analysis. The results of the research show that the English extracurricular program is capable of improving children's language skills, although several challenges in its implementation remain, especially related to teaching methods and limited time.